Technology-centered academic library partnerships and collaborations - Doherty, Brian, 1962- (IGI Global, 2016)
"This book examines cooperation efforts employed by librarians allowing them to provide more services and resources to their patrons, focusing on the utilization of available digital technologies for the improvement of library functions"--Provided by publisher.